Improving budget transparency to achieve effective and sustainable governance - Stanimirović, Tatjana (Central European Public Administration Review, 2022)
Purpose: The sustainable development concept implies the involvement of citizens in the budgetary process. Since the Covid-19 pandemic and its consequences have confirmed the importance of citizens’ involvement also in the future, the purpose of the paper is to assess the level of interest in budgetary issues as well as the reasons for budget transparency stagnation as reported for Slovenia by the Open Budget Index (OBI). Design/methodology/approach: The study relies on a combination of desk research and survey carried out among employees directly or indirectly connected to public finance issues in public sector organisations. The statistical analysis is based on 251 fully completed surveys. Findings: The results confirm the lack of political will as the main obstacle to budget transparency and the stagnation reported by the Open Budget Index for the past years, suggesting that the stronger the interest in budget transparency expressed by the respondents, the more likely they see political will as an important barrier. Academic contribution to the field: The findings of the paper contribute to the isolation and potential further development of the factors that influence the transparency of the central budget. Originality: The paper is a pioneer attempt to study central budget transparency in Slovenia, offering results that can be compared to other EU countries.
Keywords: accountability; barriers; budget; odgovornost; ovire; proračun; transparency; trasparentnost